INDUKSI KETAHANAN KEKERINGAN DELAPAN HIBRIDA KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN BORON - , FITRIYANA SHOLIHATUN; , Eka Tarwaca Susila Putra S.P, M.P., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objectives of research were 1) to determine the response and survival rates of eight oil palm hybrids to drought stress and 2) to determine the optimal dose of boron (B) that able to induce the resistance of oil palm hybrid to drought stress. The experiment was arranged in Randomized Complete Block Design (RCBD) factorial, with three blocks as replications. The first factors were the hybrids of oil palm, namely Yangambi, Avros, Langkat, PPKS 239, Simalungun, PPKS 540, PPKS 718 and Dumpy. The second factors were the boric acid applications, namely 0